Epidemiologic profile and risk factors of patients at intensive care unit, Hospital San José, Popayán - Diego Illera; Gumercindo Rivera; Andrés Eduardo Orozco; Victor Daniel Montenegro; César Orlando Vidal (Revista de la Facultad de Ciencias de la Salud, 2015)
Introduction: I.C.U. is an area dedicated to integral attention of severe ill patients. Objective: To establish the epidemiological profile of patients admitted to adult I.C.U. of Hospital Universitario San José of Popayán, Colombia, 2012. To determine risk factors associated to mortality and most prevalent diagnoses. Methods: Descriptive, retrospective study of the epidemiological profile of patients admitted to I.C.U. After authorization from ethics committee, 949 patients selected from the database were studied. Variables were codified according to investigators criteria. Associations were established among variables and mortality and diagnoses using chi² to determine statistical significance (p